## first law

vi = intial velocity
vf = final velocity
change of velocity = Vf - Vi
acceleration = change of velocity / change of time
acceleration = Vf-Vi ÷ t

at= vf - vi

## vi+at=vf 1 this the first law of motion the rule os vi+at=vf

## second law

displacement= average velocity X time
average velocity = Vi + Vf ÷ 2
d = (Vi + Vf ÷ 2 ) X t
WE SAY THAT 1st law

Vf= Vi + at
WE WILL CANCEL vf and but the rule
d = ( vi + vi + at ÷ 2) X t
= 2vit + at with power 2 ÷2

## d = vit + half at with power two

3rd law ---------- NOTE : ^ this mean with power too ok vf = vi+at by squaring vf^ = ( vi + at )^ vf ^ = vi^ + 2viat + a^t^ vf^-vi^=2viat+a^t^ = 2a(vit + half at^ )

## vf^-vi^ = 2ad

THEN THE RULE IS note :^ this mean with power two 1) Vi + at = Vf first law 2) d = vit + half at ^ second law 3) Vf^- Vi^= 2ad third law

## Comments

Sort by:

TopNewestThanks! – Sachin Vishwakarma · 1 year ago

Log in to reply

Try to code in Latex. – Sachin Vishwakarma · 1 year ago

Log in to reply